A new turbo decoding algorithm with joint time and phase estimation - Ormesher, R.; Mason, J. (Milcom 2004 - 2004 IEEE Military Communications Conference, 2004)
This report describes a new algorithm for the joint estimation of carrier phase, symbol timing, and data in a turbo coded and phase shift keyed (PSK) digital communications system. Jointly estimating phase, timing, and data can give processing gains of several dB over conventional processing, which consists of joint estimation of carrier phase and symbol timing followed by estimation of the turbo-coded data. The new joint estimator allows delay and phase locked loops (DPLL) to work at lower bit energies where turbo codes are most useful. Performance results of software simulation tests are given.